Wykorzystanie programowania genetycznego do generowania sygnałów kupna - sprzedaży instrumentów finansowych - Jóźwiak, Agnieszka (Generating Financial Trading Rules with Genetic Programming, 2007)
Technical analysis is aimed at devizing trading rules capable of exploiting short-term fluctuations on the financial markets. This market timing approach may be a profitable alternative to the buy-and- hold approach. This paper presents generating short-term trading rules on the stock market with genetic programming. Computational results, based on historical pricing data, for 4 Polish companies listed on the Warsaw stock exchange market are included.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 103-110